Pengaruh Pola Komunikasi Organisasi TerhadapKinerja Karyawan Lpp Rri Surakarta(Pola Komunikasi Antara Pimpinan dan Karyawan di Radio Republik Indonesia Surakarta) - Taufandy Yarosca, Elham, Drs.Joko Sutarso,SE.M.Si (2017)
The pattern of organizational communication is a massage system from communicator to coomunicant in order to change the behavior, opinion and attitude. The staff of RRI in running their broadcast are required to be professional and highly motivated. Staff are asked to perform theirselves as employees who are mentally good, authoritative, afficient, and aware of their responsibility to achieve maximum performance This research aimed to find out the effect of the pattern of the organizational communication on the staff performance of RRI Surakarta The method used in this research was survey to the staff of RRI Surakarta involving 34 employees. The data collection technique used questionnaire and documentation. Data analysis technique applied multiple Jiniear regression analysis. Hypothesis was confirmed by t and f tests and coefficient of determination. The result of the resrarch showed the regression result with the equivalent of Y=15.741 + 0.886X1 + 0.616X2 + 0.781X3 + e, which showed there a positive effect of the pattern organizational communication on the performance of LPP RRI Surakarta staff, Besides, it was shown that the degree of the influence was 84.2%. the influence of Communication pattern in LPP RRI Surakarta was in accordance with the results of data analysis shown that there was positive influence of communication pattern from downwards, upwards, or horizontally to employee performance of LPP PPI Surakarta viewed from the equivalence of the regression. The positive influence showed that communication pattern from downwards, upwards, or horizontally can increase the performance of the staff of LPP RM Surakarta.